Human Resource Practice and Job Satisfaction in Private College of Kathmandu - Karki, Sujata (Journal of Advanced Academic Research, 2024)
Human resource practice includes conducting job analyses, planning personnel needs, recruiting the right people for the right job at the right time, performance appraisal, orienting and training, rewarding, new job opportunities, motivate them. This study is related to the impact of HR practices on employee job satisfaction. In private colleges of Kathmandu, employees are not satisfied with their jobs even in the presence of HR practices. For this study convenience, sampling technique is used and the limitations of our study are the private colleges in Kathmandu. A questionnaire has been used to collect primary data based on structured questions. The study's hypothesis was tested through correlation and regression analysis to inspect employee satisfaction. Findings investigate a significant relationship between HR Practice and job satisfaction. Moreover, salary, reward and recognition, career advancement, promotion, new job opportunities, participation in decision-making and working environment positively affect job satisfaction. Results show that HR practices (recruitment and selection, salary, training and development, new job opportunities, rewards, recognition, and motivation) have more significant effects on employees’ job satisfaction in comparison to the Working Environment. The empirical findings concluded that best HR Practices have a significant and positive effect on employee job satisfaction. Therefore, it is clear that employers should understand and implement the HR Practices correctly to take good work from their employees. Further research may be done to achieve a high level of job satisfaction.